Acute cardiogenic pulmonary oedema with multiorgan dysfunction – still to learn more about nitrobenzene poisoning. (20th December 2011) - Agrawal, Avinash; Gutch, Manish; Arora, Rahul; Jain, Nirdesh
Abstract : Nitrobenzene is a nitrite compound often used in polishes or solvents. Its toxic effects are due to its ability to induce methaemoglobinaemia. The clinical presentation of this poisoning varies according to the concentration of methaemoglobin level in blood. The importance of early identification of the compound on the basis of clinical suspicion corroborative with methaemoglobin level with timely intervention is required to prevent fatal outcome. It is also important to take care of the secondary cycling of nitrobenzene from body stores to prevent secondary recurrence of symptoms in patients after heavy exposure. Here author reports a rare case of accidental poisoning with nitrobenzene presented with respiratory distress and cyanosis. On investigation, he was diagnosed to have cardiogenic pulmonary oedema and multiorgan dysfunction. The urgent institution of methylene blue as specific antidote along with haemodynamic and ventilatory support was proved crucial for life saving of the patient.